2010
DOI: 10.1002/mus.21736
|View full text |Cite
|
Sign up to set email alerts
|

Distributed low‐frequency functional electrical stimulation delays muscle fatigue compared to conventional stimulation

Abstract: We present a low-frequency stimulation method via multi-pad electrodes for delaying muscle fatigue. We compared two protocols for muscle activation of the quadriceps in paraplegics. One protocol involved a large cathode at 30 HZ (HPR, high pulse-rate), and the other involved four smaller cathodes at 16 HZ (LPR, low pulse-rate). The treatment included 30-min daily sessions for 20 days. One leg was treated with the HPR protocol and the other with the LPR protocol. Knee-joint torque was measured before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 36 publications
2
102
1
Order By: Relevance
“…The existence of different motor points within each of the three superficial heads of the quadriceps suggests that a change in the population of activated fibers could also be obtained through a multichannel stimulation technique that involves a non-synchronous activation of different muscle volumes. Consistently, Malesević et al (2010) recently showed in paraplegic patients that NMES delivered to one quadriceps via multi-pad electrodes (one anode positioned at the distal part of the quadriceps and four cathodes distributed over the quadriceps muscles) delayed the occurrence of fatigue with respect to a conventional stimulation (one electrode positioned over the top of the quadriceps and the other over the distal part of the muscle).…”
Section: Implications For Electrical Stimulation Procedures and Electmentioning
confidence: 67%
“…The existence of different motor points within each of the three superficial heads of the quadriceps suggests that a change in the population of activated fibers could also be obtained through a multichannel stimulation technique that involves a non-synchronous activation of different muscle volumes. Consistently, Malesević et al (2010) recently showed in paraplegic patients that NMES delivered to one quadriceps via multi-pad electrodes (one anode positioned at the distal part of the quadriceps and four cathodes distributed over the quadriceps muscles) delayed the occurrence of fatigue with respect to a conventional stimulation (one electrode positioned over the top of the quadriceps and the other over the distal part of the muscle).…”
Section: Implications For Electrical Stimulation Procedures and Electmentioning
confidence: 67%
“…On this basis, they suggested that a maximization of the spatial recruitment during NMES could also be obtained through a multi-channel stimulation technique that involves a non-synchronous activation of different muscle volumes. Interestingly, it has recently been demonstrated that asynchronous low-frequency (16 Hz) stimulation of the quadriceps muscle using a multi-pad electrode (four channels) can elicit a strong, fused contraction, though producing less muscle fatigue compared to single-channel high-frequency (30 Hz) stimulation (Malesević et al 2010).…”
Section: Nmes Methodologymentioning
confidence: 99%
“…Alternative techniques, stratagems and tools that might be able to minimize the impact of these limitations on NMES use should receive more attention. For example, the use of ''distributed'' NMES (Malesević et al 2010), multi-path stimulation with large electrodes (Feil et al 2011), and magnetic stimulation (Bustamante et al 2010) should be encouraged as opposed to the classical NMES set-up, particularly for commonly stimulated large muscles. Additionally, a world-wide consensus on standardization of NMES terminology, which should include current and contraction characteristics, is considered necessary to allow a more uniform use of NMES both in research and in clinical settings.…”
Section: Optimizationmentioning
confidence: 99%
“…For example, in voluntary muscle contractions, asynchronous motor unit discharge produces steady forces with relatively low Wring rates. A stimulation strategy aimed at achieving this asynchronous behavior is reportedly achieved by delivering electrical stimulation through multiple electrode locations on a single muscle, producing a fused contraction with relatively low stimulation rates, and delaying the onset of fatigue (Popovic and Malesevic 2009;Hughes et al 2010;Malesevic et al 2010). Voluntary muscle contractions also diVer from typical electrically stimulated contractions by their increased variability in motor unit discharge, motivating the investigation of electrical stimulation patterns with varying frequency, amplitude, and pulse width (Thomas et al 2002;Graham et al 2006;Chou and Binder-Macleod 2007;Indurthy and GriYn 2007).…”
Section: Emerging Technologies To Counter Fatigue During Nmesmentioning
confidence: 98%